meso-Hydroxylmethyl-1,3,5,7-tetramethylBODIPY: A Visible-Light Photoremovable Protective Group for Carboxyl Groups - Yang, Yong-Qing; Xu, Yue; Yuan, Junjie; Liu, Jialu; Yin, Jie; Lu, Zheng; Xu, Ximing (Synthesis, 2024)
A meso-BODIPY-type photoremovable protecting group for carboxyl group is developed. BODIPYs are well-known for brilliant color, favorable to reaction monitoring and purification. meso-BODIPY esters are achieved via esterification in 44–89% yields, while deprotection is fulfilled under irradiation of blue LED bulb in the presence of photocatalyst and organic hydrogen donor in 43–95% yields. This method is applicable to a variety of acids, such as aromatic, heteroaromatic, alkyl, α,β-unsaturated carboxylic acids, etc. Our BODIPY-deprotective condition is almost neutral that both methyl and tert-butyl esters are compatible.
Keywords: BODIPY; protective group for carboxyl group; ethidine; visible-light; photocatalyst